Implementing Project-Based Learning to Enhance 21st Century Skills Among Senior High School Students - Zuhri, Zuhri; Afriani, Gusma (Global Education Journal, 2025)
The demands of the 21st century require students to possess academic knowledge and essential life skills such as critical thinking, creativity, collaboration, communication, and digital literacy. However, traditional teaching methods often fail to cultivate these competencies effectively. This study aims to explore how Project-Based Learning (PBL) can enhance 21st-century skills among senior high school students. Using a qualitative research approach, data were collected through observations, interviews, focus group discussions, and document analysis over three months at a senior high school in Indonesia. Thematic analysis revealed that PBL significantly improved students' critical thinking, problem-solving, teamwork, communication skills, and digital literacy. Students engaged more deeply with the content and demonstrated greater autonomy, creativity, and collaboration in real-world project tasks. Despite some initial challenges, such as unfamiliarity with group-based learning and limited digital competence, students gradually developed confidence and independence. The study concludes that PBL is a powerful pedagogical model for preparing students to meet future academic and professional demands. Its contribution lies in promoting more meaningful, student-centered learning while offering insights into the conditions necessary for effective implementation in varied educational contexts.